PEMANFAATAN DAUN PALLIASA (Kleinhovia hospita L) SEBAGAI BAHAN ALTERNATIF DALAM MEMPERTAHANKAN KESEGARAN IKAN KEMBUNG (Rastrelliger sp): (The Utilization of Palliasa Leaves (Kleinhovia hospita L) as an Alternative to Sustain Quality of Mackerel (Rastrelliger sp)) - Jalil Genisa; A Nur Faidah Rahman; Kurniati Tajuddin (Hasanuddin University Food Science and Technology Study Program, 2019)
Mackerel is one of the ingredients that has perishable food. This decay can be caused by the activity of microorganisms such as Salmonella typhi, Staphlococcus aureus and Streptococcus mutanas. Palliasa leaf (Kleinhovia hospita L) is one of herbal plant from south Sulawesi is efficacious and able to act as antibacterial and antifungal. Meanwhile, palliasa leaf contains several antibacterial compounds namely alkaloids, flavonoids, and terpenoids. The purpose of this research was to know the effect of using palliasa leaf extract to freshness of mackerel during storage. Step of research were preparation of raw materials, soaking, storage and testing. Testing conducted include total microbial tests, pH values, moisture content and organoleptic testing. The treatment used was fresh fish immersion in palliasa leaf extract with concentration of 2%, 3% and 4% for 15 minutes. The results showed that soaking in palliasa leaf extract can inhibit microbial growth. Based on result of research of palliasa leaf concentration that is 2%. 3%, and 4% to freshness of mackerel during storage of room temperature can be concluded that the effectiveness of palliasa leaves in maintaining freshness of mackerel ie with palliasa leaf concentration 3% up to 8 hours longer storage than control (without soaking palliasa leaf extract) with average score of 7 (accepted). In addition, the soaking treatment of palliasa leaf extract can increase the organoleptic value of the fish. Palliasa leaf able to inhibit the growth of microorganisms.